Penggambaran Pseudosection Bawah Permukaan dari Suatu Proses Evapotranspirasi Tanaman Jagung Menggunakan Program RES2DINV - Suroso, Teguh; Yulianto, Tony; Yulianto, Gatot (BERKALA FISIKA, 2006)
The dipole-dipole investigation of one line corn crop subsurface condition have been done in relationship with evapotranspiration process. The variation of subsurface resistivity investigation occured by the caused of evapotranspiration process.The space of dipole-dipole array measured in 0,20 meter and 0,40 meter with n value from 1 to 4. In May 21st,24th,28th,31st 2005 the dipole-dipole array was measured. The electrodes and corn crop-line possition is parallel. The depiction of subsurface condition viewed by using the Res2Dinv apparent resistivity data. The depiction showed the high resistivity of the corn crop area and the transpiration process is higher than evaporation process. Anomaly resistivity value in the pseudosection output is 54,30 Wm. Keywords: dipole-dipole, evapotranspiration, resistivity